Drone based herbicide application in greengram (Vigna radiata) - RAMESH, T; MADHUSREE, S; RATHIKA, S; MEENA, S; RAJA, K (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during winter (rabi) season of 2023 at Anbil Dharmalingam Agricultural College and Research Institute, (Tamil Nadu Agricultural University), Tiruchirappalli, Tamil Nadu to assess the effect of drone based herbicide application in greengram. Results showed that drones could be effectively used for spraying of pre-emergence herbicide to control weeds and increase the yield of greengram. Further, application of pendimethalin 0.75 kg/ha with spray fluid of 60 litre/ha precisely through drones controlled the weeds effectively (WCE of 81.8%), increased grain yield, saved herbicide dose and spray fluid to the tune of 6.9%, 25% and 88% respectively than manual spray of pendimethalin 1.0 kg/ha with spray fluid of 500 litre/ ha. Thus, application of pendimethalin 0.75 kg/ha with spray fluid of 60 litre/ha was considered as the optimum dosage and spray fluid for drone spray to control weeds, increase grain yield and profit in greengram, considering the reduced dose of herbicide as well as the labour scarce situation.